ECONOMIC-STATISTICAL ANALYSIS OF THE IMPACT OF INDUSTRY ON MACROECONOMIC INDICATORS: https://doi.org/10.5281/zenodo.14534971 - Yuldasheva , Nihola (Science technology&Digital finance, 2024)
In this article, it is analyzed the influence of the industrial sector on the economic development of Uzbekistan by using statistical methods. Since the industrial network is directly related to the sphere of production and services, structural changes in this network and dynamic changes in periodic series are statistically analyzed. This is of great importance when developing the necessary criteria for stabilizing macroeconomic indicators. Using the indicators in the industrial network, it is possible to determine some forecast values ​​for future periods. For this reason, we studied the national economy and the factors influencing it using methods of correlation and regression analysis.